An ovarian Leydig cell tumor of ultrasound negative in a postmenopausal woman with hirsutism and hyperandrogenism: A case report. Issue 10 (March 2018) - Chen, Min; Zhou, Weibin; Zhang, Zhe; Zou, Yuting; Li, Chengjiang
Abstract: Rationale: The incidence of severe hyperandrogenism associated with masculinity in women is very low. While rare and difficult to diagnose, androgen secreting tumors should be suspected in women with hyperandrogenism and hirsutism, especially in the postmenopausal population. Herein we present one case of ovarian Leydig cell tumor (LCT) with markedly elevated serum testosterone levels and frank hirsutism. Patient concerns: A 60-year-old woman, presented with increased hair growth and androgenic alopecia and the hormonal laboratory examination showed that she had elevated serum testosterone level and normal dehydroepiandrosterone sulfate (DHEAS), androstenedione, 17- hydroxyprogesterone, cortisol and thyroid stimulating hormone (TSH). Diagnoses: The diagnosis of possible testosterone secreting tumor was performed when pelvic computed tomography (CT) and magnetic resonance image (MRI) showed a right adnexal mass of 15mm×16mm indicative of sex cord- stromal tumors. Interventions: The patient received laparoscopic total abdominal hysterectomy and bilateral salpingo-oophorectomy. Outcomes: After operation, testosterone got back to the normal level and clinical symptoms subsided. Lessons: It is common that postmenopausal androgen excess is a state of relative or absolute androgen excess originating from the adrenal gland and/or ovaries. In either case, doctors need to assess such patients and exclude relatively rare potential causes of tumors. Any woman who has hirsutism or frank evidence of markedly increased testosterone should exclude this kind of possibility of androgen producing tumors. It is possible to determine the origin of androgen hypersecretion with the severity of symptoms, the extent of androgen excess, and the relevant imaging studies. Since LCT are rare ovarian sex-cord stromal tumors, it can be beneficial for diagnosis with careful research of patient history of the defeminization followed by virilization, and a CT and MRI image.